Perancangan Game Edukasi Berhitung Berbasis Mobile Aplikasi Inventor - Rosdiani, Amelia; Warmansyah, Jhoni (UIN Imam Bonjol Padang, 2021)
Technological advances that are developing very rapidly have a positive impact on the development of various educational games that can be designed as a tool to stimulate aspects of early childhood development. This study aims to design a numeracy educational game based on the inventor's mobile application that can be used in early childhood education units. The method used is Educational Design Research (EDR) which is limited to a design model with stages; 1) Preliminary research; 2) Prototyping stage; 3) Phase assessment. This study resulted in the design of a numeracy educational game that can be used by PAUD units to improve numeracy skills, which is one of the aspects of cognitive development. Teachers can also design using the Inventor mobile application to improve other aspects of child development.